Advertising Appeals and Cultural Values of Video Advertising in Thailand - Cheryl, Shee Yupeh; Norazirah, Ayob (2020)
In recent years, Thailand videos advertising is generally known as the leading producer of weep-worthy viral videos in the world. Reasons for Thailand advertisements to stand out from the rest is said to be because of its commonly used advertising appeals, and cultural values focused in majority of Thailand advertisements. This research aims to study advertising appeals and cultural values in Thailand video advertisements. Specifically, the research investigates the reflection of cultural value through advertising appeal through the executional framework in Thailand video advertisements. This exploratory research employs primarily the method of ethnography in order to understand how cultural values are reflected through the advertising appeals in video advertisements from Thailand. The result shows that the most commonly used advertising appeal are Family Appeal, followed by Health Appeal and Effective Appeal. In terms of cultural values, the result shows the Thailand’s advertisements are skewed slightly higher towards collectivism and femininity. Majority of the Thailand video advertisements are using executional framework of storytelling.